2015
DOI: 10.1111/tmi.12521
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus in sub‐Saharan Africa: systematic review and metaregression on prevalence and risk factors

Abstract: Abstractobjective We systematically reviewed publications on prevalence and risk factors for gestational diabetes mellitus (GDM) in the 47 countries of sub-Saharan Africa.methods We conducted a systematic search in PUBMED and reviewed articles published until June 2014 and searched the references of retrieved articles. We explored sources of heterogeneity among prevalence proportions with metaregression analysis.results Of 1069 articles retrieved 22 studies were included. Half were from West Africa, specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
115
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 51 publications
12
115
4
1
Order By: Relevance
“…About ~7% of all pregnancies in Africa are complicated by gestational diabetes, and up to 14% of all pregnancies develop gestational diabetesrelated complications (Mwanri et al 2015). Although GDM is a major cause of prenatal and maternal morbidity in Rwanda, it is still on the rise such that by the time it peaks its effects will be confounded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About ~7% of all pregnancies in Africa are complicated by gestational diabetes, and up to 14% of all pregnancies develop gestational diabetesrelated complications (Mwanri et al 2015). Although GDM is a major cause of prenatal and maternal morbidity in Rwanda, it is still on the rise such that by the time it peaks its effects will be confounded.…”
Section: Discussionmentioning
confidence: 99%
“…The global prevalence of hyperglycemia in pregnant women 20-49 years is increasing to 16.9% affecting over 21.4 million live births, and ~90% of cases are in low-and middleincome countries (LMICs) of Africa (Mwanri et al 2015). As Africa struggles to combat infectious diseases particularly HIV infection, tuberculosis and malaria, the challenge is to cope with increasing burden of non-communicable diseases (NCDs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence and risk factors of GDM in sub-Saharan Africa seems to be high up to about 14% and heterogeneous (Mwanri et al 2015). Interestingly, prevalence of GDM is higher in women with previous stillbirth, family history of type 2 DM, and medium upper arm circumference (MUAC) above 28 cm, while women living in rural areas showed signifi cantly lower prevalence (Anzaku and Musa 2013; Mwanri et al 2015).…”
Section: Gdm In Low-income Countriesmentioning
confidence: 99%
“…Interestingly, prevalence of GDM is higher in women with previous stillbirth, family history of type 2 DM, and medium upper arm circumference (MUAC) above 28 cm, while women living in rural areas showed signifi cantly lower prevalence (Anzaku and Musa 2013; Mwanri et al 2015). In low-income countries, cheaper treatments alternative to insulin are metformin and glibenclamide but authors have suggested as more effective and acceptable strategy a prevention, as an appropriate diet and physical exercise in order to reduce the short-and long-term GDM related complications (Coetzee 2009).…”
Section: Gdm In Low-income Countriesmentioning
confidence: 99%